Integrasi Nilai-Nilai Islam Dalam Kurikulum Pendidikan Di SMP Al-Munawwir Sangatta Selatan - Juliana, Juliana; Yasin, Muhammad (JURNAL ILMU PENDIDIKAN & SOSIAL (SINOVA), 2025)
The integration of Islamic values in the educational curriculum plays an important role in shaping students' character and behavior. This study aims to analyze the application of Islamic values in the curriculum at Al-Munawwir Sangatta Selatan Junior High School, the challenges faced, and its impact on student character. The research uses a descriptive qualitative method with data collection through interviews, observations, and documentation. The results of the study show that the application of Islamic values is carried out through habits such as worship, honesty, and responsibility. The challenges faced include limited facilities, infrastructure, and inefficient teaching methods. The positive impact can be seen from the improvement of students' character, such as discipline, honesty, and good social relationships. This integration is not only important to form individuals of noble character, but also as a foundation for a moral and responsible society. Synergy between schools, families, and technology is the key to overcoming these challenges.